2021
DOI: 10.1108/dta-09-2018-0087
|View full text |Cite
|
Sign up to set email alerts
|

Applying sentiment analytics to examine social media crises: a case study of United Airline's crisis in 2017

Abstract: PurposeIn recent years, social media crises occurred more and more often, which negatively affect the reputations of individuals, businesses and communities. During each crisis, numerous users either participated in online discussion or widely spread crisis-related information to their friends and followers on social media. By applying sentiment analysis to study a social media crisis of airline carriers, the purpose of this research is to help companies take measure against social media crises.Design/methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…Infectious disease outbreaks and other health problems were widely discussed and shared on social media [ 33 , 34 ]. Sentiment analysis of social media data is emerging as an important research field and is in use at different spheres, namely, e-sports [ 35 , 36 ], sports [ 37 – 41 ] healthcare [ 42 – 44 ] and even geopolitical conflicts and crises [ 45 50 ]. Since the Covid-19 outbreak, a number of studies throughout the world have utilised Twitter data to assess the public opinion [ 21 , 28 , 51 57 ], main discussion themes [ 58 61 ] and misinformation [ 62 – 64 ] about the Covid-19 vaccine.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Infectious disease outbreaks and other health problems were widely discussed and shared on social media [ 33 , 34 ]. Sentiment analysis of social media data is emerging as an important research field and is in use at different spheres, namely, e-sports [ 35 , 36 ], sports [ 37 – 41 ] healthcare [ 42 – 44 ] and even geopolitical conflicts and crises [ 45 50 ]. Since the Covid-19 outbreak, a number of studies throughout the world have utilised Twitter data to assess the public opinion [ 21 , 28 , 51 57 ], main discussion themes [ 58 61 ] and misinformation [ 62 – 64 ] about the Covid-19 vaccine.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Based on Twitter, Kaur et al (2021) explored the impact of crisis communication strategies of Indian leaders in public health events after the outbreak of COVID-19 on the public's emotions, which can be divided into 10 types, including anger, expectation, disgust, and fear. Similarly, based on Twitter, Tian et al (2021) divided sentiments into eight categories, including arousal and valence, and examined the crisis of United Airlines' in 2017. The authors found that social media sentiment analysis can help identify public responses and help enterprises adopt appropriate communication strategies.…”
Section: Sentiment Analysismentioning
confidence: 99%
“…For paracrises constructed by multiple, sometime conflicting voices, effective responses cannot be developed without identifying and understanding influential public voices. Over the past few years, scholars and practitioners have explored various tools to examine publics' social media communication during crises, such as automated content analysis (e.g., Van Der Meer 2016) and sentiment analysis (e.g., Tian and Wang 2021). While these tools excel in identifying topics and emotions from large amounts of texts, they are limited in generating insights for prioritizing or predicting social media voices during paracrises.…”
Section: Associating Ego Network Structures With Content Viralitymentioning
confidence: 99%